THE INFLUENCE OF EDUCATIONAL INNOVATION ON THE CREATIVE DEVELOPMENT OF FUTURE SCIENCE TEACHERS - Красноштан, Ігорь (SWorldJournal, 2023)
The article substantiates the essence of innovation as a separate field of scientific knowledge. Modern requirements for the professional training of future teachers of natural sciences in the context of the development of creative professional abilities